STRATEGI PENGELOLAAN OPERASIONAL OBYEK WISATA KEBUN RAYA JOMPIE, PARE-PARE - Suryati Iskandar A; Qurrotu Aini Besila; Rini Fitri; Titiek P Debora (Universitas Trisakti, 2022)
Jompie Botanical Garden is located on Pare-pare City, South Sulawesi, serves as a conservation area for coastal flora and flora of Wallacea and is a tourist destination. The lack of Management Plan of tourist area causes the decline of Environmental Quality which has an impact on the decline of quality of tourist facilities, environmental pollution, and threats to plant diversity. The purpose of this study is to describe the operational management conditions that are currently applied to the Jompie Botanical Garden, analyze the inhibiting and supporting factors in the management, and develop operational management strategies of Jompie Botanical Garden Tourism objects. The method in this research is descriptive method with qualitative approach. Data collection techniques using observation, interviews and literature studies. Data analysis techniques using strength, Weknees, Opportunity, Threats (SWOT) analysis. The results showed the acquisition of eight alternative strategies for operational management of Jompie Botanical Garden Tourism objects, namely promoting and selling flora, fauna and nature tourism programs, re-evaluating the jompie Botanical Garden Tourism Management Plan in an integrated manner, selection of labor in accordance with the field of management expertise, improving the quality of security of Jompie Botanical, strengthening the institutional system, re-evaluation of the jompie botanical garden hygiene system, improving the quality and quantity of Jompie Botanical Gardens.